A REVIEW ON FAST DISSOLVING TABLET - Chauhan, Kalindi; Solanki, Rakesh; Sharma, Shivani (International Journal of Applied Pharmaceutics, 2018)
In the present scientific scenario, the drug delivery technology has become extremely competitive and quickly evolving with ever-increasing demand. Fast dissolving tablet (FDT) is one such style of an innovative and distinctive drug delivery system. Once FDT is placed on the tongue, it disintegrates or dissolves quickly (in seconds) without chewing or water. Fast dissolving pills became well-liked because of higher patient compliance and most popular over typical capsules and tablets. Numerous FDT products entered the market in the nineteen eighties. This novel drug delivery like FDT or mouth dissolving tablet (MDT) has overcome several disadvantages like dysphagia or non-accessibility of water whereas travel. Compared with typical dosage form FDT is an alternative as well as helpful for the patient. The basic approach employed in the development of FDT is that the use of superdisintegrants like crosspovidone, croscarmellose sodium or maximizing pore structure within the formulation. This review article contains different techniques used for preparing FDT, silent features, numerous proprietary technologies, mechanism of super disintegration, and also the limitations.